PANDEMI COVID-19 TERHADAP KEBIASAAN KONSUMSI BUAH, SUSU DAN MULTIVITAMIN PADA ORANG DEWASA DI PROVINSI JAMBI - Merita; Egy Sunanda Putra; Silvia Mawarti Perdana; Ismi Nurwaqiah (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Background: Good food selection is very important. It will help in efforts to prevent diseases such as Covid-19. Objective: To analyze the effect of Covid-19 pandemic to consumption habits of fruit, milk and multivitamin among adults in Jambi Province Methods: This research is a type of survey research conducted in April 2020. Data collection was carried out using Google forms. The sampling technique is accidental sampling. The sample is adults aged 19-59 years totaling 254 people. Data were analyzed using wilcoxon test. Results: The results showed that before the covid-19 pandemic most respondents had the habit of consuming fruits, milk and multivitamins which were classified as rare, after the existence of the Covid-19 pandemic it was classified as frequent. There was an influence of the covid-19 pandemic on fruit, milk and multivitamin consumption habits (p <0.001). Conclusion: There is an effect of the Covid-19 pandemic to the consumption habits of fruit, milk and multivitamins in adults in Jambi Province.